MICROBIOLOGICAL ASSESSMENT OF THE SHELF LIFE OF PEACH NECTAR WITH PROPOLIS AS A NATURAL PRESERVATIVE - Lozano-Lévano, César (2023)
Propolis is a resinous substance produced by bees, and various investigations show that it has antioxidant, antimicrobial, and antifungal properties, which is why it is considered a great alternative as a natural preservative for foods and beverages, compared to artificial preservatives. The objective of this research work was to microbiologically evaluate the useful life of peach nectar with propolis as a natural preservative, under the parameters of NTS N°071-MINSA/DIGESA-V.01. The methodology used consisted of preparing nectar samples with different concentrations of propolis (0.03% and 0.05%) and storing them for two, five and nine days at room temperature, subsequently performing the seeding and microbiological count for mesophilic aerobes, coliforms total, molds and yeasts. The results showed a greater antimicrobial effect on total coliforms and molds, for nectar samples with propolis at 0.05%; and a greater antimicrobial effect on yeasts and mesophilic aerobes, for samples at 0.03%. Although the shelf life of the product could not be determined due to the high initial microbial loads, the potential preservative activity of propolis is evident.